THE CONSTRUCTION OF THE FEMALE SUBJECT IN THE LYRICAL POEMS OF MARÍA JOSEFA GARCÍA GRANADOS: A PIONEER OF THE ROMANTICISM BETWEEN TWO WORLDS - Establier Pérez, Helena (Acta Literaria, 2015)
In the 1830s, in the process of adaptation of Romantic literature in America, a poet born in Spain and almost unknown outside Guatemalan literary circles, María Josefa García Granados, was already cultivating journalism, political satire in verse and also lyric poetry. Anticipating by more than a decade the appearance of Romantic feminine poetry in Spain and by almost twenty years the activity of American women writers, García Granados becomes the first woman to introduce the topics and the forms of this new literary movement on both sides of the Atlantic Ocean. The concerns and the subjects that will much later shape the canon of Romantic women’s writing appear for the first time in her lyric poems. This paper discusses some poems of María Josefa García Granados so far unnoticed both by the history of the Romanticism and by studies focusing on the work of women writers in this period.